When local meets global: Exploring multiculturalism beyond code mixing in Indonesian food endorsements on social media - Valiantien, Nita Maya; Setyowati, Ririn; Alamsyah, Alamsyah (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
The use of code-mixing in social media has amassed significant attention as social media platforms have become prominent spaces for communication in recent years. This study aims to explore how code-mixing in Instagram captions serves as a reflection of multiculturalism in Indonesia. Through content analysis of posts from the Instagram account which focus on food reviews and endorsements, this research provides insights into the intersection of language, culture, and social media in a diverse, globalized context, The source of data is from Instagram account @sobatjajan.samarinda where the posts were manually reviewed, and captions that included food-related content and employed code-mixing were selected for analysis. The findings revealed 37 relevant captions, categorized into three main themes: (1) content promoting local food from the three major ethnic groups in Samarinda, (2) posts showcasing a broader diversity of Indonesian cuisine, and (3) content featuring foreign food influences. Through a linguistic analysis of these captions, the study illustrates how code-mixing not only serves as a promotional tool but also highlights the multicultural dynamics of the region, blending local and global influences in food culture.